TI_GERICHTE 15.2011.86 vom 9. Januar 2012 , Obbligo di informare nell'ambito del pignoramento da parte di avvocati e di notai - TI Tribunale d'appello (2012)
Obbligo di informare nell'ambito del pignoramento da parte di avvocati e di notai